Field studies of a Brazilian seahorse population, Hippocampus reidi Ginsburg, 1933 - Freret-Meurer,Natalie Villar (2008)
This study was carried out to fill the gaps that remain under Hippocampus reidi biology. Analysis of variations of sex ratio, density, breeding season, distribution and home range of a population of the endangered Brazilian seahorse H. reidi from a rocky shore on Araçatiba beach, Ilha Grande, Brazil were carried out. Araçatiba beach is a tourist Environmental Protected Area, suffering antropic pressure. A fixed population of H. reidi was studied, where al lthe individuals were visually tagged and sex, reproductive state and location on site were identified from December 2002 to November 2004. A total of 20 individuals were visually tagged with a mean density of 0.18 m-2. Sex ratios were skewed, with more females than males. All the males brooded during 13 months and presented smaller home range than the females during the breeding season. The highest densities were found on shallowest areas.